2022
DOI: 10.1021/acs.bioconjchem.2c00173
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Determinants of Surface Accessibility in Staphylococcus aureus

Abstract: Bacterial cell walls represent one of the most prominent targets of antibacterial agents. These agents include natural products (e.g., vancomycin) and proteins stemming from the innate immune system (e.g., peptidoglycan-recognition proteins and lysostaphin). Among bacterial pathogens that infect humans, Staphylococcus aureus (S. aureus) continues to impose a tremendous healthcare burden across the globe. S. aureus has evolved countermeasures that can directly restrict the accessibility of innate immune protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
2

Relationship

4
0

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…57 More recently, our laboratory described the installation of click handles on the PG to systematically assess how flexibility and size of large biopolymers impact their ability to reach the PG surface. 47, 58 We reasoned that site-specific metabolic installation of a bioorthogonal reactive handle within the PG of S. aureus could also be leveraged to analyze the accumulation of antibiotics to S. aureus in phagocytic vacuoles in immune cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…57 More recently, our laboratory described the installation of click handles on the PG to systematically assess how flexibility and size of large biopolymers impact their ability to reach the PG surface. 47, 58 We reasoned that site-specific metabolic installation of a bioorthogonal reactive handle within the PG of S. aureus could also be leveraged to analyze the accumulation of antibiotics to S. aureus in phagocytic vacuoles in immune cells.…”
Section: Resultsmentioning
confidence: 99%
“…To measure the accumulation of antibiotics, we combined an assay our laboratory recently developed aimed at systematically assessing how flexibility and size of large biopolymers impact their ability to reach the peptidoglycan (PG) surface of S. aureus cells 22, 23 with one that we developed to measure the permeability of molecules into mycobacteria. 24 In this new iteration ( Figure 1B ), a strained alkyne dibenzocyclooctyne (DBCO) is metabolically installed within the PG of S. aureus . DBCO-tagged bacterial cells are then incubated with macrophages to promote their uptake.…”
Section: Resultsmentioning
confidence: 99%
“…9 Our own laboratory recently described the combination of DBCO-azide to determine the accessibility of molecules to and within Staphylococcus aureus peptidoglycan 31 and successfully miniaturized the assay for highthroughput analysis of a transposon library using 384-well plates. 32 Most relevantly, our own laboratory recently demonstrated that the combination of DBCO (metabolically anchored onto the peptidoglycan) and azide-tagged test molecules can report on permeability of small molecules across the 'myco' membrane of Mycobacteria, including in the causative agent of tuberculosis. 33 For antibiotics that do not manage to cross the OM efficiently, an alternative strategy may be the co-treatment with an adjuvant molecule that disrupts the OM thus promoting the passage of molecules to their molecular target.…”
Section: Discussionmentioning
confidence: 99%
“…To measure the accumulation of antibiotics, we combined an assay our laboratory recently developed aimed at systematically assessing how flexibility and size of large biopolymers impact their ability to reach the peptidoglycan (PG) surface of S. aureus cells [17] with one that we developed to measure the permeability of molecules into mycobacteria. [18] In this new iteration (Figure 1B), a strained alkyne dibenzocyclooctyne (DBCO) is metabolically installed within the PG of S. aureus.…”
Section: Methodsmentioning
confidence: 99%